Efficacy of cannabinoids in paediatric epilepsy. (6th November 2018) - Ali, Shayma; Scheffer, Ingrid E; Sadleir, Lynette G
Abstract : There are hundreds of compounds found in the marijuana plant, each contributing differently to the antiepileptic and psychiatric effects. Cannabidiol (CBD) has the most evidence of antiepileptic efficacy and does not have the psychoactive effects of ∆ 9 ‐tetrahydrocannabinol. CBD does not act via cannabinoid receptors and its antiepileptic mechanism of action is unknown. Despite considerable community interest in the use of CBD for paediatric epilepsy, there has been little evidence for its use apart from anecdotal reports, until the last year. Three randomized, placebo‐controlled, double‐blind trials in Dravet syndrome and Lennox–Gastaut syndrome found that CBD produced a 38% to 41% median reduction in all seizures compared to 13% to 19% on placebo. Similarly, CBD resulted in a 39% to 46% responder rate (50% convulsive or drop‐seizure reduction) compared to 14% to 27% on placebo. CBD was well tolerated; however, sedation, diarrhoea, and decreased appetite were frequent. CBD shows similar efficacy to established antiepileptic drugs. What this paper adds: Cannabidiol (CBD) shows similar efficacy in the severe paediatric epilepsies to other antiepileptic drugs. Careful down‐titration of benzodiazepines is essential to minimize sedation with adjunctive CBD. What this paper adds: Cannabidiol (CBD) shows similar efficacy in the severe paediatric epilepsies to other antiepileptic drugs. Careful down‐titration of benzodiazepines is essential to minimize sedation with adjunctive CBD. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=UvD0CrMFeLA&feature=youtu.be